THE ROLE OF EDUCATIONAL PROPHETIC TO INCREASE ACADEMIC INTEGRITY AMONG STUDENTS - Arifin Sholeh; Fitriah M. Suud (Jurnal Konseling Pendidikan Islam, 2026)
Prophetic education plays a role in improving academic integrity among students. Prophetic education is an educational approach that emulates the life and values of the Prophet Muhammad (PBUH), integrating intellectual, moral, and spiritual dimensions to form individuals with character and character. This research was conducted on students of the Islamic Religious Education Study Program, University of Muhammadiyah, focusing on their understanding of the value of integrity which includes honesty, responsibility, trust, and self-quality. The results show that most students view honesty (the trait of ṣidīq) as the main foundation of academic integrity, which encourages them to avoid dishonest behaviors such as plagiarism and conditions in exams. Professional education is considered relevant to build a healthy and ethical academic culture by prioritizing prophetic values, such as honesty and trust. The implementation of this education in higher education is expected to create a learning ecosystem that not only focuses on academic achievement but also maintains the intellectual dignity and personal integrity of students.